Toughening of carbon fibre reinforced polymer composites with rubber nanoparticles for advanced industrial applications - N. G. Ozdemir; T. Zhang; I. Aspin; F. Scarpa; H. Hadavinia; Y. Song (eXPRESS Polymer Letters)
This study investigates the effects of nano carboxylic acrylonitrile butadiene rubber (CNBR-NP) and nano acrylonitrile butadiene rubber (NBR-NP) on the interlaminar shear strength and fracture toughness of carbon fibre reinforced polymer composites (CFRP) with dicyandiamide-cured epoxy matrix. The results show that nano-size dispersion of rubber significantly improved the Mode I delamination fracture toughness (GIC) of the CFRP by 250% and its Mode II delamination fracture toughness (GIIC) by 80% with the addition of 20 phr of CNBR-NP. For the NBR-NP system, the GIC and GIIC delamination fracture toughness of the CFRP were increased by 200 and 80% respectively with the addition of 20 phr (parts per hundred rubber) of nano rubber to the matrix. Scanning electron microscopy (SEM) images of the fracture surface revealed that the toughening was mainly achieved by debonding of the nano rubber, crack path deflection and fibre bridging.